Malaria in Europe: A Historical Perspective - Boualam, Mahmoud A.; Pradines, Bruno; Drancourt, Michel; Barbieri, Rémi (Frontiers in Medicine, 2021)
Endemic malaria, which claimed 229 million new cases and 409,000 deaths in 2019 mainly in Africa, was eradicated from Europe by the mid-20th century. Historical descriptions of intermittent tertian and quartan fever reported in texts of Hippocrates in Greece and Celsus in Italy suggest malaria. A few paleomicrobiology investigations have confirmed the presence of malarial parasite Plasmodium falciparum in 1st, 2nd, and 5th century infected individuals in diverse regions of Italy, and Plasmodium sp. later in Bavaria. The causative Plasmodium pathogens, discovered in the 19th century in Algeria, were controversially used as therapeutic agents in the European pharmacopeia more than two centuries after effective quinine-based treatments had been introduced in Europe. How Europe managed to eradicate malaria and what the history of malaria was in Europe are of medical interest, and this review traces research pathways for a renewed understanding of malaria eradication in Europe through combined historical and paleomicrobiological investigations.